Dosimetry in CR mammography using radiochromic film - Mabel Bustos Flores; Arnaldo Prata Mourão; Samuel Queiroz Pelegrineli; Juraci Passos dos Reis Junior (Brazilian Journal of Radiation Sciences, 2022)
To estimate the dose that a patient's mammary tissue receives during mammographic screening, radiochromic film and objects simulators made of PMMA are used. This material interacts with X-rays in a similar way to tissue. Estimating the dose absorbed by a tissue is important to verify that the dose is within the recommended limits and in this way minimize the undesirable effects that radiation can cause and optimize the radiation dose that patients receive. This work aims to estimate the dose deposited in the breast tissue that a patient can receive during a mammographic screening, when a mammography device with a CR detection system is used. PMMA plates were used as simulator object and radiochromic film to measure the dose from its calibration curve. The dosimetric test was performed on the upper, lower surface and between the plates of the object.